La calidad de los servicios de la cooperativa de ahorro y crédito Uniandes Ltda y la fidelidad de sus clientes, periodo 2016 - 2017 - Moyón Paucar, John Jaime (2018)
The objective of the research was to determine the influence of the quality of service on customer loyalty in the UNIANDES Savings and Credit Cooperative in the 2016-2017 period. It responds to the modality of a scientific investigation, developed under the parameters of a descriptive type of research, the collection of information was based on the application of a structured questionnaire that was applied to the employees and partners of the Cooperative. As can be seen, we have the results of the qualification made to the quality of service ranges by both external and internal customers that jointly with the Savings and Credit Cooperative seek the common good, achieve an objective that is the satisfaction of customers and the institutional objective, for this reason continuous improvement is sought to reach the partners in a satisfactory manner and meet their needs at the time of acquiring our service and that they feel more identified with the institution to continue to be an important part of their developing. According to the results of the evaluation according to the SERVQUAL evaluation method, different strategies have been considered in order for the UNIANDES Savings and Credit Cooperative to improve the service and achieve customer loyalty. In addition it was possible to conclude by checking the hypothesis according to the square CHI it is observed that the calculated X² value (calculated chi2) 450.40 is greater than the value of X² Tab (tabulated chi2) "18.3070", the null hypothesis is rejected and is considered favorable the alternative hypothesis for what " The quality of the service in the UNIANDES LTDA savings and credit cooperative affects the loyalty of its customers ".